Evaluasi Tingkat Erosi Tanah KecamatanSukorejo Kabupaten Kendal - Yuliyanti, Irma; , Ir.Imron Harjono, M.Si (2016)
This research was conducted in district Sukorejo Kendal with a title: "Evaluation of the level of soil erosion in district Sukorejo Kendal", aims at: knowing the level of soil erosion in the area of research and find out the spread rate of soil erosion in an area of research. The methods used in this research is a method of field survey and laboratory analysis. Determination of the level of erosion by using USLE method. The data used in this study are land characteristics data includes rainfall, soil texture, organic matter, soil structure, soil permeability, slope length and slope data, land management, and the management of the plant. Method of sampling using stratified sampling method with the strata units of land. The results showed that the rate of soil erosion that is in the area of research has a very mild erosion classes up to very heavy with the level of erosion 1.39-535.02 ton/ha/yr. Land units that are included in the rate of erosion is very light V1S1pkbMeCLit2 = 1.39 tonnes/ha/yr, V1S1swhMeCLit3 = 1.68 tonnes/ha/yr, and V1S1tglMeMTRe2 = 5.69 tonnes/ha/yr. Unit of land that has a mild erosion rate is VIS1pkbKoGrklbLit1 = 15.04 tonnes/ha/yr, VIS1tglMeCLit2 = 16.85 tonnes/ha/yr, V1S1pkbAndCReC3 = 50.85 tonnes/ha/yr, V1S1pkbMeMTRe3 = 56.35 tonnes/ha/yr, and V1S1tglKoGrklbLit3 = 57.2 tonnes/ha/yr. Unit of land included in the heavy erosion rate is V1V2pkbAndCReC5 = 157.9 tonnes/ha/yr and V1S1tglMeCLit3 = 256.95 tonnes/ha/yr. Whereas the unit of land which has a very heavy erosion rate is V1V2swhAndCReC7 = 535.02 tonnes/ha/yr. The research results are presented in a map of a level soil erosion Sub Sukorejo scale 1: 100.000.